Let´s not talk about it. Feminism and populism in Argentina - Martínez Prado, Natalia (2020)
Since the emergence of #NiUnaMenos [Not One Less] in 2015, feminism has become widespread in Argentina. Nowadays, actions such as to identify oneself as a feminist, to cite her slogans, to use her handkerchiefs, to hold her flags, are no longer conceived as minority, elitist or radicalized practices. In this essay we aim to offer an exploratory account of the conditions that have made this unusual scenario possible. In particular, we consider how the heterogeneous groups that gathered under the scream 'Ni Una Menos!' have become part of a feminist 'us'. That is, what were the conditions that enabled the current expansion of what is known as the green and violet tide of feminism? How have the feminists? demands articulated multiple claims and dimensions of social protest related to economic, social, cultural and racial issues? With these questions in mind, we will begin by exploring how this expansion has been addressed by the existing literature, focusing on the approach of Graciela Di Marco, in whose view this process must be understood within the framework of the successful construction of a 'feminist people'. Taking on this approach? while nonetheless marking our differences? we will go on to explain the conditions that from our perspective enabled feminism to become popular. Firstly, we will point to the relationship that feminist groups have established with human rights activism since the early 80s. Later, we will direct attention to the effects of displacement resulting from the political articulation that took place in the new millennium between human rights groups and the political force that was in government for almost a decade, Kirchnerism. As we will show, this political process decisively affected the feminist movements and the positions they hold in the social and political arena at the present time.